2022
DOI: 10.3389/fimmu.2022.837842
|View full text |Cite
|
Sign up to set email alerts
|

Human B Cells Mediate Innate Anti-Cancer Cytotoxicity Through Concurrent Engagement of Multiple TNF Superfamily Ligands

Abstract: The essential innate immunity effector cells, natural killer and dendritic cells, express multiple plasma membrane-associated tumor necrosis factor (TNF) superfamily (TNFSF) ligands that, through simultaneous and synergistic engagement, mediate anti-cancer cytotoxicity. Here, we report that circulating B cells, mediators of adaptive humoral immunity, also mediate this innate anti-cancer immune mechanism. We show that resting human B cells isolated from peripheral blood induce apoptosis of, and efficiently kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…The scRNA-seq data of patients with HNSCC were obtained from the GEO database (GSE164690) ( 8 ). The data were integrated using the SCTransform method of R software Seurat package and analysed using mutual principal component analysis (PCA).…”
Section: Methodsmentioning
confidence: 99%
“…The scRNA-seq data of patients with HNSCC were obtained from the GEO database (GSE164690) ( 8 ). The data were integrated using the SCTransform method of R software Seurat package and analysed using mutual principal component analysis (PCA).…”
Section: Methodsmentioning
confidence: 99%
“…Janjic and colleagues demonstrated that the resting human B lymphocytes derived from peripheral blood can induce efficient killing of leukemia and solid tumor cells. 61 B cells from the circulation expressed transmembrane tumor necrosis factor (TNF) superfamily (TNFSF) ligand, including TNF, Fas ligand, lymphotoxin (LT) α1β2, and TNF-related apoptosis-inducing ligand (TRAIL). Evidence showed that B cells from patients with head and neck squamous cell carcinoma (HNSCC) expressed decreased levels of TNFSF ligands and exhibited reduced cytotoxicity compared to those from healthy individuals.…”
Section: Genes Regulating B Cells Functions In the Tmementioning
confidence: 99%
“…Evidence showed that B cells from patients with head and neck squamous cell carcinoma (HNSCC) expressed decreased levels of TNFSF ligands and exhibited reduced cytotoxicity compared to those from healthy individuals. 61 Recent studies have demonstrated B cell maturation antigen (BCMA), also known as tumor necrosis factor receptor superfamily member 17 (TNFRSF17) and CD269, was preferentially expressed in mature B cells, and its overexpression and activation were related to multiple myeloma (MM) development. The conversion of membrane-bound BCMA to soluble BCMA (sBCMA) through the action of γ-secretase was noteworthy, especially since higher serum levels of sBCMA have been observed in MM patients, where it correlates with poorer prognosis.…”
Section: Genes Regulating B Cells Functions In the Tmementioning
confidence: 99%
See 1 more Smart Citation
“…This secretion, in turn, could contribute to Th1/Th2 polarization of T cells or boost the responses of T cells [ 37 ]. Furthermore, the possible defensive effect of B cells in cancer is shown by CpG-activated B cells that utilize TNF-related apoptosis inducing ligand (TRAIL/Apo-2L)-dependent mechanisms to attack tumor cells [ 38 , 39 ]. The existence of this function of mediating anti-cancer cytotoxicity is further strengthened by the induction of an increase in granzyme B levels in B-chronic lymphocytic leukemia cells when treated with IL-21 and CpG oligodeoxynucleotide [ 39 , 40 ].…”
Section: Antibody Diversity and Cancermentioning
confidence: 99%